Prediction of anticancer peptides derived from the true lectins of Phoenix dactylifera and their synergetic effect with mitotane - Baothman, Othman; Ali, Ehab M. M.; Hosawi, Salman; Hassan E. Konozy, Emadeldin; Abu Zeid, Isam M.; Ahmad, Abrar; Altayb, Hisham N. (Frontiers in Pharmacology, 2024)
Background and aims: Cancer continues to be a significant source of both illness and death on a global scale, traditional medicinal plants continue to serve as a fundamental resource of natural bioactive compounds as an alternative source of remedies. Although there have been numerous studies on the therapeutic role of Phoenix dactylifera, the study of the role of peptides has not been thoroughly investigated. This study aimed to investigate the anticancer activity of lectin peptides from Phoenix dactylifera using in silico and in vivo analysis.Methods: Different computational tools were used to extract and predict anticancer peptides from the true lectins of Phoenix dactylifera. Nine peptides that are bioactive substances have been investigated for their anticancer activity against MCF-7 and T47D (two forms of breast cancer). To counteract the unfavorable effects of mitotane, the most potent peptides (U3 and U7) were combined with it and assessed for anticancer activity against MCF-7 and HepG2.In silico analysis revealed that nine peptides were predicted with anticancer activity. In cell lines, the lowest IC50 values were measured in U3 and U7 against MCF-7 and T47D cells. U3 or U7 in combination with mitotane demonstrated the lowest IC50 against MCF-7 and HepG2. The maximum level of cell proliferation inhibition was 22% when U3 (500 mg/mL) and 25 mg/mL mitotane were combined, compared to 41% when 25 mg/mL mitotane was used alone. When mitotane and U3 or U7 were combined, it was shown that these bioactive substances worked synergistically with mitotane to lessen its negative effects. The combination of peptides and mitotane could be regarded as an efficient chemotherapeutic medication having these bioactive properties for treating a variety of tumors while enhancing the reduction of side effects.